(untitled) (International Journal of Engineering and Computer Science, 2013)
Over speed limit violation done by public transport (buses) is a common problem in most of major roads in Tanzania. This has been reported to be one of the traffic accident causes in Tanzania. Moreover road accidents in Tanzania have been incessant and to bar the loss of life due to accidents is more crucial. This research work proposed and implemented a prototype called Automatic Vehicle Over Speed Accident Alert and Locator System (AVOAALS). The system uses GPS and GSM network, especially GPRS function of the GSM network. The system monitors the speed and accident event of the bus. Once an event is detected, the system leads the current position of the bus using GPS. The event, bus registration number and position data are sent to the control database server as SMS via GPRS services of the GSM Network. The event, bus registration number and position data are then stored in the data base. SMS application software was developed using Microsoft visual studio package. Microsoft SQL saver was used for storing data because of its high performance query engine, tremendously fast data insert capability and strong support for specialized web functions. Using this SMS application software, end user was able to receive SMS on any standard mobile phone about event, position of the targeted object, date and time of event. The administrator at the control data base server was able to extract reports about accident and over speed offenders. This system is very much useful for monitoring speed limit violations, reckless driving, and minifying the accident occurrence as well as optimizing rescue operations. The system was implemented using Sunrom’s GPS receiver with active antenna, GSM modem SIM900D, PIC18F4520 Microcontroller, mobile phone handset Nokia 110 and laptop computer. Prototype was tested and worked perfectly notifying nearby police station, hospital and fire station whenever appropriate event occurred. This work extends the utilization of mobile communication coverage on major roads in Tanzania to enhance road safety.